Short tandem repeats shared by B- and C-hordein cDNAs suggest a common evolutionary origin for two groups of cereal storage protein genes - Forde, Brian G. (1985)
We have identified cDNA clones coding for the major sulphur-rich and sulphur-poor groups of barley storage proteins (the B- and C-hordeins, respectively). Hybridization studies have revealed unexpected homologies between B- and C-hordein mRNAs. Using a deletion mutant (Risø 56), we have mapped some C-hordein-related sequences within, or closely associated with, B-hordein genes at the Hor 2 locus. Nucleotide sequencing has shown that the primary structure of B-hordein polypeptides can be divided into at least two domains: domain 1 (repetitive, proline-rich, sulphur-poor), which is homologous to C-hordein sequences, and domain 2 (non-repetitive, proline-poor, sulphur-rich), which makes up two-thirds of the polypeptide and is partially homologous to a 2S globulin storage protein found in dicotyledons. The coding sequences that are homologous in B- and C-hordein mRNAs have an asymmetric base composition (>80% C-A) and are largely composed of a degenerate tandem repeat based on a 24 nucleotide consensus that encodes Pro-Gln-Gln-Pro-Phe-Pro-Gln-Gln. We discuss the evolutionary implications of the domain structure of the B-hordeins and the unusual relationship between the two groups of barley storage proteins.